Comparison of techniques for detecting antigens of Giardia lamblia and Cryptosporidium parvum in faeces. - Tee, G H (1993)
AIM--To compare the use of commercial monoclonal antibody test systems--the Giardia CEL IF test and the Crypto CEL IF test--for the detection of Giardia lamblia and Cryptosporidium parvum antigens in faeces with conventional techniques. METHODS--Sensitivity and specificity were evaluated using preparations of cysts of G lamblia and purified oocysts of C parvum. Evaluation of 59 random faecal samples passing through the Department of Clinical Parasitology, Hospital for Tropical Diseases, London, was carried out for both organisms. RESULTS--The fluorescence staining techniques proved more sensitive than other tests routinely used for diagnosis.